Pengaruh Promosi dan Kualitas Pelayanan terhadap Keputusan Pembelian Ulang (Studi Kasus pada Surplus 88) - Desrianty Machmud, Suci; Wijaya, Mahendra; N Rahmanto, Andre (Bahtera Inovasi, 2023)
In increasingly fierce coffee shop competition marked by the significant growth in the number of coffee shops in recent years, extra efforts need to be made to understand consumer needs and desires. A better understanding of these aspects can be used as a reference in developing marketing strategies to increase consumer repurchases. This is the background for this research to analyze the factors that drive repeat purchase decisions. This research conducted a case study on Start Up Coffee Gorontalo. The population in this research are consumers who visit Surplus 88. Multiple linear regression analysis techniques were used to test the research hypothesis. The research results found that promotions and service quality can significantly encourage repurchase interest. To encourage repeat purchases, promotions need to be intensified by providing attractive discounts, providing membership cards with various attractive rewards, offering products at competitive prices, and offering cross promotions with other products. Intention to repurchase is also influenced by service quality which can be improved by ensuring employees appear neat, provide professional service, provide fast and responsive service, employees understand well the various products offered, and employees can communicate well with customers